The Palaearctic types of Chrysididae (Insecta, Hymenoptera) deposited in the Linsenmaier collection. Part 6. Parnopini: genus Parnopes Latreille; Chrysidini: genus Euchroeus Latreille and Stilbum Spinola - Rosa, Paolo; Heim, René; Bernasconi, Marco Valerio (Zootaxa, 2026)
An illustrated catalogue of the Palaearctic types of Parnopes Latreille, 1797, Euchroeus Latreille, 1809 and Stilbum Spinola, 1806 described by Walter Linsenmaier is presented. In total, Linsenmaier described one species and one subspecies of Parnopes, 24 species and 13 subspecies of Euchroeus and eight subspecies of Stilbum. Of these, two Parnopes taxa, 20 Euchroeus and four Stilbum are from the Palaearctic region. Primary types of these taxa are deposited in the collection of the Natur-Museum in Luzern, Switzerland, with the sole exceptions of the holotype of Euchroeus (Euchroeus) eous ssp. arabicus Linsenmaier, 1994a and of Parnopes indicus Linsenmaier, 1968 which are deposited in the collection of the Natural History Museum in London (UK). This catalogue includes the list of the described species, photographs of 24 primary types and a synthesis of the recent changes in the taxonomy of Euchroeus.